Investigating English Teachers' Teaching Style on Students' Engagement in EFL Classrooms - Rosalia, Harnita (PT ARRUS Intelektual Indonesia, 2024)
This research aimed to discover: (1) the teaching styles applied by the English teachers at SMA Negeri 1 Bone, and (2) the most influential teaching styles toward students’ engagement at SMA Negeri 1 Bone. A qualitative methodology was utilized, with two English teachers and eight students serving as the subjects. Data were collected through observation, audio-video recording, and interviews. They were analyzed using a qualitative approach based on the four-step process outlined by Miles and Huberman: data collection, data display, data condensation, and conclusions drawing/verifying. The results of the research revealed that (1) the English teachers at SMA Negeri 1 Bone applied three teaching styles, namely expert style, formal authority style, and facilitator style and the dominant teaching styles used by the first teacher were expert and facilitator style while the dominant teaching style used by the second teacher was formal authority style and facilitator style (2) the researcher elaborated students’ engagement into three categories such as behavioral engagement (e.g., participation, attention), emotional engagement (e.g., enthusiasm, mood), and cognitive engagement (e.g., thinking critically, problem-solving). The facilitator style was the most influential teaching style on student engagement, which emphasizes teacher-student interaction. When students are actively involved in the learning process and the teacher employs diverse teaching strategies, students become more interested in learning. Furthermore, the teachers attempted to create an engaging learning environment by incorporating games and humor, which improved student engagement.